Prognostic value of MRD in CLL patients with comorbidities receiving chlorambucil plus obinutuzumab or rituximab - Langerak, Anton W; Ritgen, Matthias; Goede, Valentin; Robrecht, Sandra; Bahlo, Jasmin; Fischer, Kirsten; Steurer, Michael; Trněný, Marek; Mulligan, Stephen P; Mey, Ulrich J M; Trunzer, Kerstin; Fingerle-Rowson, Günter; et al. (Blood, 2019)
Publisher's Note: There is a Blood Commentary on this article in this issue.
Keywords: Neoplasm, Residual; Rituximab; Comorbidity; Chlorambucil; protinádorové látky; Antineoplastic Combined Chemotherapy Protocols; prognóza; Adult; Aged; dospělí; Prospective Studies; senioři; rituximab; humanizované monoklonální protilátky; komorbidita; Antibodies, Monoclonal, Humanized; Leukemia, Lymphocytic, Chronic, B-Cell; senioři nad 80 let; lidé; Humans; reziduální nádor; protokoly protinádorové kombinované chemoterapie; Aged, 80 and over; chlorambucil; Prognosis; chronická lymfatická leukemie; lidé středního věku; Antineoplastic Agents; Middle Aged; prospektivní studie